Acute effects of mustard, horseradish, black pepper and ginger on energy expenditure, appetite, ad libitum energy intake and energy balance in human subjects - Gregersen, N. T.; Belza, A.; Jensen, M. G.; Ritz, C.; Bitz, C.; Hels, O.; Frandsen, E.; Mela, D. J.; Astrup, A. (British journal of nutrition, 2013)
Chilli peppers have been shown to enhance diet-induced thermogenesis (DIT) and reduce energy intake (EI) in some studies, but there are few data on other pungent spices. The primary aim of the present study was to test the acute effects of black pepper (pepper), ginger, horseradish and mustard in a meal on 4 h postprandial DIT. The secondary aim was to examine the effects on subjective appetite measures, ad libitum EI and energy balance. In a five-way placebo-controlled, single-blind, cross-over trial, twenty-two young (age 24·9 (sd 4·6) years), normal-weight (BMI 21·8 (sd 2·1) kg/m2) males were randomly assigned to receive a brunch meal with either pepper (1·3 g), ginger (20 g), horseradish (8·3 g), mustard (21 g) or no spices (placebo). The amounts of spices were chosen from pre-testing to make the meal spicy but palatable. No significant treatment effects were observed on DIT, but mustard produced DIT, which tended to be larger than that of placebo (14 %, 59 (se 3) v. 52 (se 2) kJ/h, respectively, P= 0·08). No other spice induced thermogenic effects approaching statistical significance. Subjective measures of appetite (P>0·85), ad libitum EI (P= 0·63) and energy balance (P= 0·67) also did not differ between the treatments. Finally, horseradish decreased heart rate (P= 0·048) and increased diastolic blood pressure (P= 0·049) compared with placebo. In conclusion, no reliable treatment effects on appetite, EI or energy balance were observed, although mustard tended to be thermogenic at this dose. Further studies should explore the possible strength and mechanisms of the potential thermogenic effect of mustard actives, and potential enhancement by, for example, combinations with other food components.